Implementasi Manajemen Strategik pada Puskesmas Berbasis BPJS: Studi Kualitatif di Puskesmas Ogotua - Purwadhi, Purwadhi; Widjaja, Yani Restiani; Rilistyawati, Nabila Distiara; Humaera, Namira Nita (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the implementation of strategic management in a community health center (puskesmas) within the framework of the Indonesian National Health Insurance (BPJS Kesehatan). Using a qualitative approach, data were collected through in-depth interviews with the head of the health center, medical staff, and patients, supported by observation and documentation. The findings reveal that the Ogotua Health Center applies strategic management by strengthening primary health care services to reduce unnecessary referrals, improving administrative systems for BPJS claims, and conducting continuous community education about participants’ rights and obligations. Challenges identified include limited human resources, particularly the shortage of physicians, and recurrent technical disruptions in the BPJS digital system, which slow down service delivery. Despite these barriers, the health center mitigates the issues through intensive coordination with BPJS regional offices and monthly evaluation meetings involving all staff. From the patient’s perspective, the service is generally perceived as fast, friendly, and accessible, although sporadic drug stock-outs remain a concern. This study concludes that strategic management contributes significantly to improving the quality and efficiency of BPJS-based services at the primary care level. Future studies should explore digital innovation, supply chain governance, and patient education strategies to further strengthen the role of puskesmas as the frontline of Indonesia’s health system.